SYMBOLISM IN THE STRUCTURE OF THE CREATIVE METHOD OF IVAN FRANKO - Holod, R. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is devoted to the investigation of the symbolistic poetics in Ivan Franko creative work. On the basis of the obtained results the conclusion has been made. It includes the fact that the symbolism was the meaningful and unseparable part of the author’s aesthetic consiousness.